Recent Advances on Cytotoxic Sesquiterpene Lactones - Quintana, José; Estévez, Francisco (Current Pharmaceutical Design, 2018)
Sesquiterpene lactones are naturally occurring compounds that have attracted considerable attention because to their vast array of biological activities. These plant-derived compounds contain the α-methylene-γ- butyrolactone functional group, which is the structural requirement for their pharmacological activities. Many of them exhibit cancer cell cytotoxicity and are promising anticancer agents through multiple mechanisms of action. Sesquiterpene lactones are alkylating agents that form covalent adducts in vivo and inhibit enzymes and key proteins. They are also potent apoptotic inducers in several cancer cells. This kind of cell death is recognized as a property that is useful for identifying anticancer drugs. This review focuses on the advances on cytotoxic sesquiterpene lactones and specifically the signal transduction pathways of cell death triggered in cancer cells.
Keywords: mitogen-activated protein kinases